Development of mobile application for onsite equipment data collection - Li, Yee Ling (2018)
Digital technology has been emerging gradually since the 19th century. Among all the devices that are introduced to the public, mobile device seems to be the most common gadget that is affordable and vital to everyone. Mobile devices have been improving continuously in both functionality, usability and design that can bring convenience to the users. These devices are commonly used in many fields, such as marketing, business, industries, faculties, government, and many others. In this project, the focus is to explore the use of mobile device in industries, as they are to fully utilize the reputation of mobile devices by changing from paperwork to electronical gadgets and applications to improve the efficiency and productivity of their workers. This project is tasked to develop a user-friendly Android-based mobile application for industries to manage their data collection onsite. The idea of this project is to provide a solution for the workers to use this application in their daily work and collect required information as well as maintaining environment sustainability by going paperless through this application. This application provides the easiest way to collect data and retrieve it from the database as well as to save the data in the device. This report stated the process of software development including documentation research of using the IDE, software planning, software design, software construction and software testing. The result of this project is believed to be presenting a customized functionable application for the related industries. This user-friendly application will bring convenience to users in completing their work effectively and efficiently.